Application of overruling in Peruvian law - Morocco Colque, Edwin Adolfo (2024)
The overruling technique, through which courts can deviate from binding precedents and establish new ones, is a highly significant practice in law, as it enables a legal system to adapt to social demands while also addressing errors that courts may have made. Based on this premise, the objective of this article is to describe the challenges faced by the application of overruling in Peru. To achieve this, an extensive bibliographic review was conducted, as well as an analysis of cases in which this mechanism was applied. It is concluded that these challenges revolve around the reasons supporting overruling, the temporal effects its application may have, and the conditions for its use. Furthermore, it is inferred that the application of this mechanism does not undermine judicial independence; on the contrary, it prevents the rigidification of jurisdictional criteria, as it provides judicial systems with constant updates and legal certainty.